The Role of International Treaties in Combating Cyber Terrorism: A Legal Analysis - Karamifar, Farhad; Tabibian, Shirin; Rezaei, Seyed Ali (Legal Studies in Digital Age, 2023)
This article explores the evolving threat of cyber terrorism and the role of international treaties in combating this complex issue. As digital technologies advance, cyber terrorism has emerged as a significant global threat, capable of disrupting critical infrastructure, economies, and national security. The article reviews the existing international legal frameworks, including the Budapest Convention on Cybercrime, and assesses their effectiveness in addressing cyber terrorism. It examines key treaties and agreements, such as UN resolutions and regional initiatives, while highlighting the challenges of enforcing these treaties due to jurisdictional issues, sovereignty concerns, and the divergence of national laws. The article also evaluates the impact of rapidly evolving technologies, such as artificial intelligence and encryption, on legal frameworks, emphasizing the need for legal reforms to address new forms of cyber attacks. By providing recommendations for harmonizing national and international laws, improving cooperation and data sharing, and integrating modern technologies into legal frameworks, this article proposes a more cohesive approach to combating cyber terrorism. Ultimately, it argues that strengthening international legal cooperation and embracing technological advancements will be crucial for effectively curbing cyber terrorism and ensuring global security.